Pengaruh Strategi Pembelajaran Aktif, Inovatif, Kreatif, Efektif, dan Menyenangkan terhadap Hasil Belajar PAK-BP Siswa Kelas IX Di SMP Katolik Gonzaga Tomohon - Hadi Ignatius Untu; Shefry Yanny Fransisco Topit (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2023)
This study aims to find out how PAIKEM learning strategies are applied to class IX students at Gonzaga Tomohon Catholic Middle School in the subject of Catholic Religious Education and Moral Education (PAK-BP), and to determine whether or not there is an influence between PAIKEM learning strategies on PAK learning outcomes. -BP class IX student at Gonzaga Tomohon Catholic Middle School. The research method used is a quantitative research method with a survey approach and is a type of causal associative research that aims to determine whether or not there is an influence or relationship between the independent variable (X) on the dependent variable (Y). The research sample in this study amounted to 88 respondents obtained by calculating the Slovin formula. Validity and reliability tests were carried out using IBM SPSS 16 For window and all questionnaire items and tests distributed were declared valid and reliable. The results of this study indicate that there is an influence between PAIKEM learning strategy variables on PAK- BP learning outcomes of class IX students at Gonzaga Tomohon Catholic Middle School with a correlation coefficient of determination of 0.443 with a percentage of 44.3% and is in the medium category with a significance of 0.000. The PAIKEM learning strategy belongs to the very good category with an average score of 83.06 on a scale of 20-80. PAK-BP learning outcomes of class IX students belong to the high category with an average score of 85.82. This shows that there is an influence between the independent variables on the dependent variable with a contribution of 44.3% and the remaining 55.7% is influenced by other factors. Based on this research, the better the PAIKEM learning strategy is applied, the better the PAK-BP learning outcomes obtained by students.